2005
DOI: 10.1111/j.1365-3156.2004.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa isolates recovered from clinical and environmental samples in Buea, Cameroon: current status on biotyping and antibiogram

Abstract: Summaryobjective The 1 study was aimed at determining the prevalent biotypes of Pseudomonas aeruginosa in the environment of Buea and the susceptibility of isolates to antibiotics.methods One hundred and fifty clinical specimens (urine, wound and sputum) collected from patients attending various health institutions in Buea, and 50 environmental swabs from furniture, appliances and surroundings of these institutions were screened for P. aeruginosa using standard microbiological and biochemical methods. Antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
(25 reference statements)
8
24
2
Order By: Relevance
“…The bacterium can cause serious infections in immunocompromised patients such as those with surgery wounds or severe burns (Sule et al, 2002;Dale et al, 2004). Result of this study showed that the prevalence of P. aeruginosa was 20.42% (29/142) among all the samples for patients and hospital environment, which is less than that reported in other studies; (39.1%) to that obtained by Okon et al (2009) from wound swabs in Nigeria and 25.5% was reported in Cameron (Ndip et al, 2005). But these results were higher than 17.85% recorded in the teaching hospital of Al-Sulaimania city, Iraq (Ekrem et al, 2014) and 18.6% reported in Egypt (Gad et al, 2007).…”
Section: Discussioncontrasting
confidence: 52%
“…The bacterium can cause serious infections in immunocompromised patients such as those with surgery wounds or severe burns (Sule et al, 2002;Dale et al, 2004). Result of this study showed that the prevalence of P. aeruginosa was 20.42% (29/142) among all the samples for patients and hospital environment, which is less than that reported in other studies; (39.1%) to that obtained by Okon et al (2009) from wound swabs in Nigeria and 25.5% was reported in Cameron (Ndip et al, 2005). But these results were higher than 17.85% recorded in the teaching hospital of Al-Sulaimania city, Iraq (Ekrem et al, 2014) and 18.6% reported in Egypt (Gad et al, 2007).…”
Section: Discussioncontrasting
confidence: 52%
“…Two isolates of each bacterial species (both gram positive and gram negative) were obtained from different clinical specimens from health centres within the study area by standard culture techniques and further identified by biochemical techniques using API 20E (BioMerieux SA) kit as described (Ndip et al, 2005).The isolates were maintained during the study period by subculturing every 48 hours on nutrient agar. The required suspension of bacteria was prepared equivalent to McFarland standard 1 (1x10 8 CFUs/ml) in 0.85% NaCl ( aq ) and crosschecked and adjusted by the standard plate count method (Black, 1996).…”
Section: Antibacterial Sensitivity Test (A) Organismsmentioning
confidence: 99%
“…The Kirby-Bauer disc-diffusion test, which conforms to the recommended standard of the Clinical and Laboratory Standards Institute (CLSI), formerly National Committee for Clinical Laboratory Standards (NCCLS), was used as previously described (15,25). Briefly, a small inoculum of each pure bacterial isolate was emulsified in 3 mL of sterile normal saline in Bijou bottles, and the density was com-pared with a barium chloride standard (0.5 McFarland).…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…Zhou et al employed biotyping as an effective means to the investigation and surveillance of S. Typhimurium-associated nosocomial infection (14); their findings demonstrated a link between infection in children and bacteria in hospital environments and carriers of medical staff. In the present study, we employed biotyping and antibiogram previously reported in our laboratory (15) as they offer advantages to smaller laboratories, such as ours, which are not optimally equipped.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation